The Effectiveness Of Neuro Linguistic Programming To Increase Students’ Confidence In Learning English For Islamic Junior High School Students - Mohammad Qushoy; Rudi Hartono; Sri Wuli Fitriati; Dwi Anggani Linggar Bharati (Prosiding Seminar Nasional Pascasarjana, 2023)
There are a lot of methods in teaching English for students. An ideal teacher will always change the method to help students to accelerate their mastery to the skills. In the past decades the language teachers used methods and techniques which did not emphasize much on the neurological aspect of language learning of the students. Amongst the numerous reasons, there are also challenges the learner faces that are psychological in nature. The objective of this study is to evaluate the effectiveness of Neuro Linguistic Programming (NLP) for language Learning especially the confidence of Islamic junior high school students. The study used quasi experimental design by performing pretest and the post-test on the experimental and control groups, the effect of the NLP treatment sessions on the experimental group was investigated for two months. The results of this study confirmed that NLP not only provides the techniques and solutions to the issue, but it also helps students to increase their confidence to learn English. In this study, NLP showed to have a significant effect on EFL learning, however, it is necessary to conduct further research to validate the results of this kind of innovative study.